Analysıs Of The Determınatıon Of Fırm Value: Fınancıal Performance As Moderatıon - Aviv Tihan; Aoliyah Firasati (Cita Konsultindo Research Center, 2024)
How society views a company affects its value. Generally, energy sector companies are negatively assessed for their operational actions towards environmental pollution and social welfare. Through the practice of efficiency, transparency, accountability and sustainability, it affects the level of trust of potential investors in providing funding to the company, which has implications for the company's value. This study aims to analyze the linkage of the influence of good corporate governance practices and corporate social responsibility on firm value with financial performance as moderation. The population of this study, are companies that are members of IDXENERGY in 2020 - 2022. With purposive sampling as a research sampling technique. Researchers apply several criteria that are in accordance with the needs and 15 companies are taken as samples in the study. The analysis technique used in this research is Panel Data Regression with the help of software such as Excel, E-Views 12 and SPSS. Based on the research results, Good Corporate Governance and Corporate Social Responsibility have a significant and positive effect on firm value. The moderating variable of financial performance can be able to strengthen the relationship between Good Corporate Governance and Corporate Social Responsibility on firm value.